DEIKSIS DALAM 21 CERITA RAKYAT BUMI LANCANG KUNING - Nahdiani Nahdiani; Auzar Auzar; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: This study describes the types of deixis in 21 Cerita Rakyat Lancang Kuning. The purpose of this study is to discuss and explain the types of deixis in 21 Cerita Rakyat Lancang Kuning. This study uses a type of qualitative research not quantitative or numbers. Supporting techniques in this study use techniques documentation. Deiksis in 21 Cerita Rakyat Lancang Kuning found, namely, (a) person deixis, (b) place deixis, and (c) discourse deixis. Based on the results of data analysis Known as the first type of single person deixis is saya, aku, hamba, daku, andan, patik, ananda, and Fatimah (nama) as self substitutes and the first persona is found are us and the awak. The second person deixis found is hulubalang, baginda, dinda, kanda, tuan muda, nek, datuk, dayang, bunda, ongku, and datuok. Personal deixis three found is ia, mereka, kalian, dan beliau, deixis where found is di sini, di sana. Sana. Ke sana, ini, and itu,, and discourse deixis are anafora and katafora.Key Words: Deixis, Deixis Type, 21 Cerita Rakyat Lancang Kuning.